Soil biotic and abiotic effects on seedling growth exhibit context-dependent interactions: evidence from a multi-country experiment on Pinus contorta invasion - Nuske, Susan J. (2021)
The success of invasive plants is influenced by many interacting factors, but evaluating multiple possible mechanisms of invasion success and elucidating the relative importance of abiotic and biotic drivers is challenging, and therefore rarely achieved. We used live, sterile or inoculated soil from different soil origins (native range and introduced range plantation; and invaded plots spanning three different countries) in a fully factorial design to simultaneously examine the influence of soil origin and soil abiotic and biotic factors on the growth of invasive Pinus contorta. Our results displayed significant context dependency in that certain soil abiotic conditions in the introduced ranges (soil nitrogen, phosphorus or carbon content) influenced responses to inoculation treatments. Our findings do not support the enemy release hypothesis or the enhanced mutualism hypothesis, as biota from native and plantation ranges promoted growth similarly. Instead, our results support the missed mutualism hypothesis, as biota from invasive ranges were the least beneficial for seedling growth. Our study provides a novel perspective on how variation in soil abiotic factors can influence plant–soil feedbacks for an invasive tree across broad biogeographical contexts.